Methane-flow system within the Nyegga pockmark field, offshore mid-Norway - Dupré, Stéphanie; Foucher, Jean-Paul; Pierre, Catherine; Decker, Carole; Westbrook, Graham; Ker, Stephan; Olu, Karine; Donval, Jean-Pierre; Charlou, Jean-Luc; Blanc-Valleron, Marie-Madeleine; Nouzé, Hervé (Frontiers in Earth Science, 2023)
We investigated fluid seepage within the Nyegga pockmark field (600-900 m water depths) off mid-Norway from ROV dives at the so-called CNE sites (CNE01 to CNE17). The seafloor morphology of some of these features corresponds to pockmarks and adjacent ridges, with the latter being the focus of present seepage activity. These structures are underlain by chimneys above a gas-charged zone with, in some cases, a substantial body of hydrate-invaded sediment (down to 1.3 s in two-way travel time at CNE03). Present-day methane-rich fluid seepage through the seabed is indicated by chemosynthetic fauna, in particular Siboglinidae polychaetes (Oligobrachia haakonmobiensis webbi and Sclerolinum contortum), microbial mats and associated Rissoidae gastropod (Alvania sp.) grazers, and confirmed by measured in-situ bottom-water methane anomalies, up to 2130 nL/L. No free-gas bubble emissions were observed or acoustically identified. The presence of authigenic carbonates reveals past seepage with very low δ13C values (down to -58‰) indicating that the major source of carbon was methane carried by the venting fluids. The ages of major periods of methane venting are provided by vesicomyid bivalve shells (Isorropodon nyeggaensis) present in two sedimentary layers, 14930 and 15500 14C yr BP (ca. 17238 and 17952 cal yr BP), respectively, corresponding to the time of Melt Water Pulse IA. The seafloor morphology and pattern of seepage -chemosynthetic fauna and microbial mat distribution and dissolved methane concentration- are remarkably heterogeneous. Pore-water chemistry profiles in a gravity core taken only 40 m from major seepage sites indicate no seepage and anaerobic methane oxidation at a sub-bottom depth of about 2 m. Present-day seepage from the studied pockmark-chimney fluid-flow system charged with gas hydrate is dominated by the advection of methane solution in pore water. Some of this methane could result from the dissolution of hydrate in the chimney, most of which would have formed during an earlier period (post-LGM times) of history of the chimney, when it was venting free gas. However, the presence of free gas beneath this chimney is probably why the water entering the chimney is already saturated with methane and the process of hydrate formation in the chimney continues today.